The Yellow Dog Contract: An Explanation (Quarterly Journal of Economics, 1933)
Journal Article An Explanation Get access The Quarterly Journal of Economics, Volume 48, Issue 1, November 1933, Page 194, https://doi.org/10.2307/1884803 Published: 01 November 1933